DNA aptamers: the game-changers in diagnostics - Abdul Rashid, Nur Nadiah; Mohd Nasir, Mohd Hamzah; Hamzah, Nurasyikin; Abdul Hamid, Azzmer Azzar; Mohamed Suffian, Izzat Fahimuddin (Kulliyyah of Science, IIUM, 2024)
Rapid and efficient diseasediagnosis is crucialfor prompt clinical intervention.The current diagnosis methods require improvements, in terms of sensitivity, specificity,and cost.Aptamers, which are synthetic oligonucleotides, have gained popularityin the diagnostic biosensors’ development as theydetect analytes, viruses, and even cancerous cellswith high accuracy.They are selected through SELEX or in silico SELEX, leading to sequences thatbindwithspecific targetsand form aptamer-target complexes.Recently, DNA aptamers are preferredcompared to RNA aptamersin many studies, due to theirstability and ability to be chemically modified.The cost-effectivenessof aptamersenhancesresearch accessibility, facilitates large-scale production,andsupports the affordability ofdiagnostics, includingthe production of POCT kits.This paper discusses the structure fundamentaland motifsofDNA aptamerssuch as hairpin,G-quadruplex,and pseudoknot.The aptamer-based diagnostic platformsin detectingvarious diseasesand the challenges of DNA aptamers are highlightedin this review